Method for improving impact resistance of concrete by fully utilizing old mortar on surface of recycled coarse aggregate

By weakening the regenerated coarse aggregate and spraying the polyurea coating, the problem of poor bonding of the regenerated concrete interface is solved, and its explosion-proof and impact resistance is significantly improved.

CN119774904AActive Publication Date: 2025-04-08WUHAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510273621.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

Old mortar on the surface of recycled coarse aggregate leads to poor bonding, high porosity, and strong water absorption, which significantly reduces the compressive strength of recycled concrete.

Method used

By weakening the regenerated crude aggregate, including soaking in a weak acid aqueous solution or pre-cracking treatment in a rotating cylinder, the compactness and strength of the old mortar is reduced, and a polyurea coating is formed to improve the impact resistance of the interface.

Benefits of technology

Under impact load, the old mortar crushing absorbs energy, preserves the integrity of the main material, and significantly improves the explosion-proof and impact resistance of recycled concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774904A_ABST
    Figure CN119774904A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the impact resistance of concrete by fully utilizing old mortar on the surface of recycled coarse aggregate, and belongs to the technical field of building materials. The method comprises the following steps that S1, the recycled coarse aggregate is weakened, pretreated recycled coarse aggregate is obtained, and the elasticity modulus of old mortar on the surface of the pretreated recycled coarse aggregate is 15%-80% of the elasticity modulus of old mortar on the surface of the original recycled coarse aggregate; s2, reacting an isocyanate component and an amino compound in solvent oil to obtain a polyurea coating, and then spraying the polyurea coating on the surface of the pretreated recycled coarse aggregate to obtain a modified recycled coarse aggregate; and S3, preparing the recycled concrete by using the modified recycled coarse aggregate obtained in the step S2. By utilizing the characteristics of high brittleness, low elastic modulus, low strength and the like of the weak old mortar on the surface of the recycled coarse aggregate, the old mortar is firstly crushed under explosion and impact loads to absorb impact energy, the integrity of a main body material is preserved, and the anti-explosion and anti-impact properties of the recycled concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for making full use of old mortar on the surface of recycled coarse aggregate to improve the impact resistance of concrete. Background Art

[0002] Crushing waste concrete into recycled coarse aggregate and applying it to new concrete structures has good environmental and economic benefits. However, the surface of recycled coarse aggregate is inevitably bonded to the old cement mortar, resulting in poor adhesion, high porosity and strong water absorption in the transition zone between recycled coarse aggregate and new mortar, which significantly reduces the compressive strength and other properties of recycled concrete.

[0003] At present, a large number of studies are focused on strengthening the performance of recycled coarse aggregate, including physical, chemical and biological strengthening methods. The ideas for strengthening recycled coarse aggregate are mainly divided into two categories: 1) using technical means to remove or reduce the old mortar on the surface of recycled coarse aggregate; 2) improving the density of the transition zone between the recycled coarse aggregate and the old cement mortar interface through the filling or chemical reaction of microparticles, and improving the adhesion of the interface transition zone. The first strengthening idea includes: physical methods such as mechanical grinding, heating grinding, particle shaping, and chemical methods such as pickling. The second strengthening idea includes: mineral admixture modification, carbonization strengthening, microbial mineralization deposition and other methods. For example, Chinese patent CN110436837A discloses a renewable concrete and a preparation method thereof, and the modification method of the modified recycled aggregate adopted includes the following steps: mechanical activation, acidification treatment, filling treatment, and coating treatment. The invention removes old mortar and edges on the surface of concrete particles through mechanical activation, dissolves the hardened cement slurry on the surface of concrete particles in the acid solution through acidification treatment, strengthens the interface transition zone of the recycled concrete, and then allows nano-fillers to enter the gaps of the acidified concrete particles through filling treatment to enhance the structural strength of the aggregate. Finally, the recycled aggregate is encapsulated in a resin network to increase the adhesion between the aggregates and the compressive strength of the concrete.

[0004] At present, there are many studies on the strengthening methods of recycled coarse aggregate, with different principles, but most of them are complicated procedures, high costs, low profitability, low cost performance, and difficult to promote and apply in engineering. Summary of the invention

[0005] In view of the deficiencies of the above prior art, one of the objects of the present invention is to provide a method for making full use of the old mortar on the surface of recycled coarse aggregate to improve the impact resistance of concrete; the present invention no longer achieves large-scale application of recycled coarse aggregate by strengthening it, but starts from the opposite side, selects recycled coarse aggregate of suitable particle size, and weakens it, and utilizes the characteristics of the old mortar with weak surface of recycled coarse aggregate, such as large brittleness, low elastic modulus, and low strength. Under explosion and impact loads, the old mortar is first broken to absorb the impact energy, thereby preserving the integrity of the main material and improving the explosion and impact resistance of recycled concrete, thereby realizing high added value and large-scale application of recycled coarse aggregate.

[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0007] A method for making full use of old mortar on the surface of recycled coarse aggregate to improve the impact resistance of concrete comprises the following steps:

[0008] S1. Weakening the recycled coarse aggregate, specifically, the steps are as follows: soaking the recycled coarse aggregate in a weak acid aqueous solution, and / or, placing the recycled coarse aggregate in a rotating drum having a toothed ring thorn on the inner surface for rotation, to obtain pre-treated recycled coarse aggregate; the elastic modulus of the old mortar on the surface of the pre-treated recycled coarse aggregate is 15% to 80% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate;

[0009] S2. The isocyanate component and the amino compound are reacted in solvent oil to obtain a polyurea coating, and then the polyurea coating is sprayed on the surface of the pretreated recycled coarse aggregate to form a polyurea coating on the surface of the pretreated recycled coarse aggregate to obtain a modified recycled coarse aggregate;

[0010] S3. Preparing recycled concrete using the modified recycled coarse aggregate obtained in step S2.

[0011] The present invention performs acid-washing pretreatment on the recycled coarse aggregate to reduce the density of the old mortar slurry and the strength of the old mortar to ensure that it is preferentially crushed under high strain rate loads; and / or, by placing the recycled coarse aggregate in a rotating drum with toothed ring thorns on the inner surface and then rolling it at high speed, the recycled coarse aggregate collides with the toothed ring thorns in the rotating drum to generate stress concentration, causing the old mortar slurry to crack and produce microcracks. When used, the microcracks of the old mortar slurry rapidly expand under high strain loads to consume impact energy. In summary, the present invention uses weak acid aqueous solution immersion and / or rotating drum pre-cracking weakening treatment to ultimately make the elastic modulus of the old mortar on the surface of the pretreated recycled coarse aggregate to be 15% to 80% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate. The old mortar on the surface of the modified recycled coarse aggregate is first broken under high strain load to absorb the impact energy and preserve the integrity of the main material; finally, the polyurea coating is sprayed on the surface of the weakened recycled coarse aggregate. Polyurea is a high molecular elastic polymer. Due to the rupture of hydrogen bonds between its hard and soft segments under high strain rate loads, it can absorb and dissipate a large amount of energy, and exhibits excellent anti-explosion and impact resistance. When the polyurea coating is sprayed on the surface of the recycled coarse aggregate, when the shock wave reaches the interface of the old mortar-polyurea coating, due to the huge difference in impact strength between the two, the old mortar cannot bear the high strain rate load transmitted by the polyurea coating, and thus breaks to absorb the capacity, while preserving the integrity of the recycled coarse aggregate body and improving the anti-explosion and impact resistance of the recycled concrete.

[0012] Preferably, in step S1, the content of old mortar on the surface of the recycled coarse aggregate is 18%wt~30%wt. When the content of old mortar on the surface of the recycled coarse aggregate is too low, the impact energy consumption is too low, and the shock wave passes through the old mortar layer and reaches the coarse aggregate layer, and the impact resistance cannot be improved; when the content of old mortar on the surface of the recycled coarse aggregate is too high, the cracks in the old mortar layer penetrate each other, forming through cracks in the recycled concrete, and the integrity of the main material cannot be guaranteed.

[0013] Preferably, the particle size of the recycled coarse aggregate is 25-40 mm. In order to ensure the residual amount of old mortar on the surface of the recycled coarse aggregate, the particle size of the recycled coarse aggregate should not be too small, so the present invention selects recycled coarse aggregate with a particle size of 25-40 mm.

[0014] Preferably, in step S1, the mass concentration of the weak acid aqueous solution is 0.3% to 1.0%, and the immersion time is 0.5 to 2 hours.

[0015] The mass concentration of the weak acid aqueous solution and the immersion time are within the specified range of the present invention, which can reduce the density of the old mortar slurry, while ensuring that the acid washing does not cause the old mortar to fall off, so that the elastic modulus of the old mortar on the surface of the pretreated recycled coarse aggregate is 15% to 80% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate.

[0016] Preferably, the pH value of the weak acid aqueous solution is 4.5-6.0.

[0017] Preferably, the weak acid aqueous solution is an aqueous solution of at least one of carbonic acid, nitrous acid, acetic acid, hypochlorous acid and hydrofluoric acid.

[0018] Preferably, the recycled coarse aggregate is put into a rotating drum having toothed ring thorns on the inner surface, and then rotated at 150-500 rpm for 20-40 minutes.

[0019] The rotation speed and time of the rotating drum are within the specified range of the present invention, which can cause the old mortar slurry to crack and produce micro cracks, so that the elastic modulus of the old mortar on the surface of the pretreated recycled coarse aggregate is 15% to 80% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate.

[0020] Preferably, the rotating drum comprises an inner rotating drum, an intermediate filter screen and an outer drum shell, the toothed annular thorns are arranged on the inner surface of the inner rotating drum and are evenly distributed along the circumferential direction of the inner rotating drum, and the cross section of the toothed annular thorns is triangular. When the rotating drum rotates, the recycled coarse aggregate collides with the tip of the toothed annular thorns.

[0021] More preferably, the aperture of the intermediate filter is 15-20 mm, so as to ensure that the tiny old mortar particles that fall are discharged, while the recycled coarse aggregate is still retained in the cylinder.

[0022] Preferably, the preparation process of step S2 and step S3 should not be irradiated by ultraviolet rays. The polyurea coating will age after being irradiated by ultraviolet rays, resulting in reduced energy consumption capacity.

[0023] Preferably, in step S3, the pouring of the recycled concrete is completed within 5 hours after spraying the polyurea coating.

[0024] Preferably, the isocyanate component includes at least one of aromatic isocyanate, aliphatic isocyanate and polyisocyanate, the amino compound includes at least one of diamine, polyamine and amino-terminated polyether, and the solvent oil includes at least one of toluene, cycloalkyl base oil and No. 150 solvent oil.

[0025] Preferably, the molar ratio of the isocyanate component to the amino compound is (1.2:1) to (0.95:1.05).

[0026] Preferably, the thickness of the polyurea coating is 3-5 mm.

[0027] Preferably, the preparation method of the polyurea coating comprises the following steps:

[0028] P1. Weigh the isocyanate component, amino compound and solvent oil into a glass reactor, heat to 90~105℃, remove water under vacuum, and react for 30~60min;

[0029] P2. Lower the temperature in the reactor to 60°C, add water and react for 10-20 minutes to remove the unreacted isocyanate component;

[0030] P3. The temperature in the reactor was raised to 90 ° C again, an additive was added, vacuum degassing was performed, and stirring was performed at a speed of 100 to 300 rpm for 1 to 5 min to obtain the polyurea coating.

[0031] More preferably, the auxiliary agent includes at least one of a defoamer, a catalyst, a dewatering agent, a dispersant, and a curing agent.

[0032] Preferably, the recycled coarse aggregate is obtained by crushing waste concrete with a strength of 25MPa-40Mpa.

[0033] Preferably, the strength grade of old mortar on the surface of the recycled coarse aggregate is M5-M15, and the mud content of the recycled coarse aggregate is less than 4%wt.

[0034] Another object of the present invention is to provide recycled concrete prepared by the method, comprising the following components in parts by weight: 750-920 parts of modified recycled coarse aggregate, 120-800 parts of fine aggregate, 150-225 parts of cement, 130-195 parts of fly ash, 140-310 parts of water, and 3-20 parts of admixture.

[0035] Another object of the present invention is to provide application of recycled concrete prepared by the method in anti-riot and anti-impact protective structures.

[0036] Compared with the prior art, the present invention is beneficial in that:

[0037] (1) The present invention no longer improves the performance of recycled concrete by strengthening recycled coarse aggregate, but instead improves the explosion resistance and impact resistance of recycled concrete by actively breaking and sacrificing the weak link (old mortar) of recycled coarse aggregate.

[0038] (2) The existing technologies for improving recycled concrete are all achieved by strengthening recycled coarse aggregate, which has the problems of cumbersome procedures and high cost, making it difficult to promote and apply in engineering. The present invention directly utilizes the weak link of recycled coarse aggregate, without modifying the recycled coarse aggregate. The technical path is simple, easy to implement, cost-effective, and can achieve high added value utilization of bulk construction waste concrete.

[0039] (3) The present invention sprays polyurea elastomer on the surface of recycled coarse aggregate to form an energy dissipation difference at the interface between the old mortar of recycled coarse aggregate and the polyurea coating. The old mortar cannot bear the high strain rate load transmitted by the polyurea coating, thus breaking to absorb the energy, while preserving the integrity of the recycled coarse aggregate. This method achieves directional crushing of microscopic materials through artificially created energy dissipation capacity differences, making the recycled concrete material significantly designable.

[0040] (4) The present invention can significantly improve the explosion resistance and impact resistance of recycled concrete, making it applicable to a wide range of scenarios and realizing large-scale application of recycled concrete, which has significant ecological and economic effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A schematic diagram of a rotating drum used in the method of the present invention;

[0042] Among them, 1. rotating cylinder; 2. driving gear; 3. base; 4. motor; 5. track; 6. support; 7. outer cylinder shell; 8. middle filter screen; 9. inner rotating cylinder; 10. tooth ring thorn. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The method of the present invention fully utilizing the old mortar on the surface of recycled coarse aggregate to improve the impact resistance of concrete comprises the following steps:

[0045] S1. Weakening the recycled coarse aggregate, specifically, the steps are as follows: soaking the recycled coarse aggregate in a weak acid aqueous solution, and / or, placing the recycled coarse aggregate in a rotating drum having a toothed ring thorn on the inner surface for rotation, to obtain pre-treated recycled coarse aggregate; the elastic modulus of the old mortar on the surface of the pre-treated recycled coarse aggregate is 15% to 80% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate;

[0046] S2. The isocyanate component and the amino compound are reacted in solvent oil to obtain a polyurea coating, and then the polyurea coating is sprayed on the surface of the pretreated recycled coarse aggregate to form a polyurea coating on the surface of the pretreated recycled coarse aggregate to obtain a modified recycled coarse aggregate;

[0047] S3. Preparing recycled concrete using the modified recycled coarse aggregate obtained in step S2.

[0048] The content of old mortar on the surface of the recycled coarse aggregate is 18%wt~30%wt. For example, it can be 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc.

[0049] The strength grade of the old mortar on the surface of the recycled coarse aggregate is M5-M15, for example, it can be M5, M7.5, M10, M15, etc.

[0050] The mud content of the recycled coarse aggregate is lower than 4.0%, for example, it can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, etc.

[0051] The weak acid aqueous solution is an aqueous solution of at least one of carbonic acid, nitrous acid, acetic acid, hypochlorous acid and hydrofluoric acid.

[0052] The molar ratio of the isocyanate component to the amino compound is (1.2:1) to (0.95:1.05).

[0053] The isocyanate component includes at least one of aromatic isocyanate, aliphatic isocyanate and polyisocyanate; the amino compound includes at least one of diamine, polyamine and amino-terminated polyether; and the solvent oil includes at least one of toluene, cycloalkyl base oil and No. 150 solvent oil.

[0054] In the following embodiments and comparative examples, the original compressive strength of the waste concrete is 26.9 MPa (obtained through actual measurement), the content of old mortar on the surface of the recycled coarse aggregate is 18%wt~30%wt; the fine aggregate is natural river sand with a particle size of 0-5mm and a fineness modulus of 2.4; the cement is Huaxin 42.5 ordinary Portland cement; the fly ash uses Grade I fly ash produced by Wuhan Yangluo Power Plant; the admixture is a polycarboxylic acid-based high-efficiency water reducing agent with a water reduction rate of 22~28%.

[0055] like Figure 1As shown, the homemade rotating drum used in the following embodiments and comparative examples includes a rotating drum 1, which is installed on a base 3 through a support 6. A driving gear 2 and a motor 4 are also provided on the base 3. A crawler 5 is connected between the rotating drum 1 and the driving gear 2. The motor 4 drives the driving gear 2 to rotate, and the driving gear 2 drives the rotating drum 1 to roll at high speed through the crawler 5; the rotating drum 1 includes an internal rotating drum 9, an intermediate filter screen 8 and an external drum shell 7. The inner surface of the internal rotating drum 9 is arranged with toothed ring thorns 10 every 30° along the circumferential direction, and the toothed ring thorns 10 are arranged in a row every 20mm along the axial direction of the internal rotating drum 9; the aperture of the intermediate filter screen is 15mm-20mm; the motor 4 is started, and the recycled coarse aggregate inside the rotating drum 1 is driven to roll through the circumferential rotation of the rotating drum 1. The recycled coarse aggregate collides with the toothed ring thorns 10 in the rotating drum 1 to generate stress concentration, causing the old mortar slurry to crack and produce microcracks.

[0056] Example 1

[0057] This embodiment provides a method for making full use of old mortar on the surface of recycled coarse aggregate to improve the impact resistance of concrete, comprising the following steps:

[0058] S1. The waste concrete is crushed into concrete blocks of about 100mm×100mm×100mm by manual pneumatic picks, and then fed into the feeding port of the jaw crusher. After mechanical crushing, recycled coarse aggregate with a particle size of 25-40mm is selected for standby use;

[0059] S2. The recycled coarse aggregate obtained in step S1 is soaked in a hypochlorous acid solution for 1.5 hours, wherein the mass fraction of hypochlorous acid in the hypochlorous acid solution is 0.45%, the pH value is 5.2, and the recycled coarse aggregate is washed with water and drained for later use;

[0060] S3. The recycled coarse aggregate obtained in step S2 is put into a homemade rotating drum at a rotating drum speed of 150 rpm for 20 minutes to obtain pretreated recycled coarse aggregate; the elastic modulus of the pretreated recycled coarse aggregate surface old mortar is 50.9% of the elastic modulus of the original recycled coarse aggregate surface old mortar;

[0061] S4. 100g of isophorone diisocyanate (IPDI) (mass fraction 90%), 89g of polyoxypropylene diamine (mass fraction 98%, average molecular weight 230) and 20g of xylene were placed in a glass reactor, heated to 95±5°C, vacuum-dried and reacted for 30 minutes; then the temperature in the reactor was lowered to 60°C, 20ml of water was added, reacted for 15 minutes, and the unreacted isocyanate was removed; then the temperature in the reactor was raised to 90°C again, silicone defoamer TEGO (mass fraction 0.1%) and organic bismuth catalyst E20 were added, vacuum-defoamed, stirred for 1 minute, and the stirring speed was 200 rpm to obtain a polyurea coating; then the obtained polyurea coating was sprayed onto the surface of the recycled coarse aggregate using an air gun to form a polyurea coating with a thickness of 3mm to obtain a modified recycled coarse aggregate;

[0062] S5. The modified recycled coarse aggregate obtained in step S4 is used to prepare recycled concrete, wherein the prepared recycled concrete comprises the following components in parts by weight: 810 parts of modified recycled coarse aggregate, 370 parts of fine aggregate, 185 parts of cement, 160 parts of fly ash, 245 parts of water, and 12 parts of admixture;

[0063] S6. The recycled concrete prepared in step S5 is cast into a cylindrical specimen with a size of Φ100mm×50mm, cured in a standard curing room for 28 days, and then subjected to a single impact dynamic compression test. The specific test process is as follows: an angle grinder is used to grind the surfaces of both ends of the specimen with high precision until the average flatness of the loading surface is less than 0.03mm. A single impact dynamic compression test is performed on the recycled concrete specimen using an SHPB tester. Friction-reducing plates are attached to the loading surfaces at both ends of the specimen. The impact air pressure of the transmitter is set to seven levels of 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, and 0.7MPa. Each group of tests contains 3 cylindrical specimens.

[0064] In this embodiment, all preparation processes were not irradiated with ultraviolet rays, and the pouring of the recycled concrete was completed within 2 hours after the polyurea coating was sprayed.

[0065] Example 2

[0066] The method of this embodiment is substantially the same as that of Embodiment 1, except that the thickness of the polyurea coating in step S4 is 4 mm.

[0067] Example 3

[0068] The method of this embodiment is substantially the same as that of Embodiment 1, except that the thickness of the polyurea coating in step S4 is 5 mm.

[0069] Example 4

[0070] The method of this embodiment is basically the same as that of Embodiment 1, except that step S2 is omitted in this embodiment, and the elastic modulus of the obtained pretreated old mortar on the surface of the recycled coarse aggregate is 77.6% of the elastic modulus of the original old mortar on the surface of the recycled coarse aggregate.

[0071] Example 5

[0072] The method of this embodiment is basically the same as that of Embodiment 1, except that step S3 is omitted in this embodiment, and the elastic modulus of the obtained pretreated old mortar on the surface of the recycled coarse aggregate is 69.8% of the elastic modulus of the original old mortar on the surface of the recycled coarse aggregate.

[0073] Example 6

[0074] The method of this embodiment is basically the same as that of Embodiment 1, except that step S2 is as follows: soaking the regenerated coarse aggregate obtained in step S1 in a hypochlorous acid solution for 0.5 hour, wherein the mass fraction of hypochlorous acid in the hypochlorous acid solution is 1.0% and the pH value is 4.7, and then scooping out, washing, and draining the water for later use; step S3 is as follows: putting the regenerated coarse aggregate obtained in step S2 into a self-made rotating drum, the rotating drum speed is 500 rpm, and rotating for 40 minutes, and the elastic modulus of the old mortar on the surface of the obtained pretreated regenerated coarse aggregate is 20.3% of the elastic modulus of the old mortar on the surface of the original regenerated coarse aggregate.

[0075] Comparative Example 1

[0076] The method of this comparative example is basically the same as that of Example 1, except that steps S2 to S4 are omitted; that is, this comparative example directly uses the recycled coarse aggregate with a particle size of 25-40 mm obtained in step S1 to prepare recycled concrete.

[0077] Comparative Example 2

[0078] The method of this comparative example is basically the same as that of Example 1, except that the modified recycled coarse aggregate obtained in step S4 is irradiated under ultraviolet light for 4 hours before pouring the recycled concrete.

[0079] Comparative Example 3

[0080] The method of this comparative example is basically the same as that of Example 1, except that the mass fraction of hypochlorous acid in the hypochlorous acid solution in step S2 is 1.5%, the pH value is 3.2, and the immersion time is 4 hours; the elastic modulus of the old mortar on the surface of the obtained pretreated recycled coarse aggregate is 9.06% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate.

[0081] Comparative Example 4

[0082] The method of this comparative example is basically the same as that of Example 1, except that the rotation speed of the homemade rotating drum in step S3 is 500 rpm, and it rotates for 60 minutes. The elastic modulus of the old mortar on the surface of the pretreated recycled coarse aggregate obtained is 11.2% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate.

[0083] Comparative Example 5

[0084] The method of this comparative example is basically the same as that of Example 1, except that step S2 and step S3 are omitted and the recycled coarse aggregate is not pretreated.

[0085] Comparative Example 6

[0086] The method of this comparative example is basically the same as that of Example 1, except that, in step S1, recycled coarse aggregate with a particle size of 16-31 mm is selected for standby use.

[0087] The dynamic stress-strain curves of the recycled concrete samples of Examples 1 to 6 and Comparative Examples 1 to 6 were sorted and analyzed, and the load strain rate was calculated according to the following method: :

[0088] The input load is ;

[0089] The output load is ;

[0090] The average stress of the specimen is ;

[0091] The displacement of the two ends of the specimen is ;

[0092] ;

[0093] The average strain of the specimen is ;

[0094] The average strain rate is ;

[0095] Based on the uniformity assumption: ;

[0096] The average strain rate of the specimen is calculated as ;

[0097] In the above formula, E, A0, and C0 are the elastic modulus, cross-sectional area, and stress pulse velocity of the SHPB tester member; A s , L s is the cross-sectional area and thickness of the specimen; ε i (t), ε r (t), ε t(t) is the strain signal of the incident wave, reflected wave and transmitted wave. The test results are shown in Table 1.

[0098] Table 1 Dynamic compression mechanical properties of recycled concrete samples

[0099]

[0100] From the test results in Table 1, it can be seen that the dynamic compression peak stress of the recycled concrete sample obtained by the method of the present invention under the impact air pressure of 0.5 MPa is 100.51~249.13 MPa, which is 100.25%~396.37% higher than that of the recycled concrete sample of Comparative Example 1 (dynamic compression peak stress is 50.19 MPa), which shows the effectiveness of the method of the present invention.

[0101] By comparing Examples 1 to 3, it can be seen that as the thickness of the polyurea coating increases, the impact resistance of the configured recycled concrete is significantly improved, and the thickness of the polyurea coating can be designed according to the expected target of the material.

[0102] By comparing Example 1 with Examples 4-5, it can be seen that the impact resistance of the recycled concrete sample is weakened by the weakening treatment of weak acid immersion or rotating drum pre-cracking alone.

[0103] Compared with Example 1, the modified recycled coarse aggregate of Comparative Example 2 was irradiated with ultraviolet rays, which caused the polyurea coating to age and reduce its energy consumption capacity, and the dynamic compression peak stress under 0.5 MPa impact pressure was reduced from 122.09 MPa to 89.18 MPa.

[0104] Compared with Example 1, in Comparative Example 3, the recycled coarse aggregate is immersed in a strong acid solution, and the rotating drum of Comparative Example 4 is operated at a high speed for a long time, so that the old mortar on the surface of the recycled coarse aggregate is peeled off, the residual mortar is significantly reduced, and there is not enough old mortar to resist the shock wave under the impact load, so that the impact resistance of the recycled concrete is reduced.

[0105] Compared with Example 1, the old mortar on the surface of the recycled coarse aggregate in Comparative Example 5 was not weakened, resulting in a decrease in the energy dissipation difference at the interface between the old mortar and the polyurea coating, which significantly weakened the impact resistance of the recycled concrete sample.

[0106] Compared with Example 1, the particle size of the recycled coarse aggregate in Comparative Example 6 is too small, the residual amount of old mortar on the surface of the recycled coarse aggregate is low, and there is not enough old mortar to resist the shock wave under the impact load, which reduces the impact resistance of the recycled concrete.

[0107] In summary, the present invention uses the old mortar on the surface of recycled coarse aggregate to improve the impact resistance of recycled concrete. The recycled coarse aggregate is first weakened by immersion in a weak acid aqueous solution and / or pre-cracking with a rotating drum, and then a polyurea elastomer is sprayed on the surface of the recycled coarse aggregate to artificially create a difference in energy dissipation capacity at the interface between the old mortar and the polyurea coating. Under high-speed shock waves, the weak link (old mortar) of the recycled coarse aggregate is actively broken and sacrificed to absorb and consume energy, thereby achieving a significant improvement in the impact resistance of the recycled concrete.

[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for making full use of old mortar on the surface of recycled coarse aggregate to improve the impact resistance of concrete, characterized in that: The following steps are involved: S1. Weakening the recycled coarse aggregate, specifically, the steps are as follows: soaking the recycled coarse aggregate in a weak acid aqueous solution, and / or, placing the recycled coarse aggregate in a rotating drum having a toothed ring thorn on the inner surface for rotation, to obtain pre-treated recycled coarse aggregate; the elastic modulus of the old mortar on the surface of the pre-treated recycled coarse aggregate is 15% to 80% of the elastic modulus of the old mortar on the surface of the original recycled coarse aggregate; S2. The isocyanate component and the amino compound are reacted in solvent oil to obtain a polyurea coating, and then the polyurea coating is sprayed on the surface of the pretreated recycled coarse aggregate to form a polyurea coating on the surface of the pretreated recycled coarse aggregate to obtain a modified recycled coarse aggregate; S3. Preparing recycled concrete using the modified recycled coarse aggregate obtained in step S2.

2. The method according to claim 1, characterized in that In step S1, the content of old mortar on the surface of the recycled coarse aggregate is 18%wt~30%wt.

3. The method according to claim 1, characterized in that In step S1, the mass concentration of the weak acid aqueous solution is 0.3% to 1.0%, and the soaking time is 0.5 to 2 hours.

4. The method according to claim 1, characterized in that The recycled coarse aggregate is put into a rotating drum with toothed ring thorns on the inner surface, and then rotated at 150-500 rpm for 20-40 minutes.

5. The method according to claim 1, characterized in that: The rotating cylinder comprises an inner rotating cylinder, a middle filter screen and an outer cylinder shell. The toothed ring thorns are arranged on the inner surface of the inner rotating cylinder and are evenly distributed along the circumferential direction of the inner rotating cylinder. The cross section of the toothed ring thorns is triangular.

6. The method according to claim 1, characterized in that The preparation process of step S2 and step S3 must not be irradiated by ultraviolet rays.

7. The method according to claim 1, characterized in that In step S3, the pouring of the recycled concrete is completed within 5 hours after the polyurea coating is sprayed.

8. The method according to claim 1, characterized in that The isocyanate component includes at least one of aromatic isocyanate, aliphatic isocyanate and polyisocyanate; the amino compound includes at least one of diamine, polyamine and amino-terminated polyether; and the solvent oil includes at least one of toluene, cycloalkyl base oil and No. 150 solvent oil.

9. The recycled concrete prepared by the method according to any one of claims 1 to 8, characterized in that: The invention comprises the following components in parts by weight: 750-920 parts of modified recycled coarse aggregate, 120-800 parts of fine aggregate, 150-225 parts of cement, 130-195 parts of fly ash, 140-310 parts of water and 3-20 parts of admixture.

10. Use of the recycled concrete prepared by the method according to any one of claims 1 to 8 in anti-riot and anti-impact protective structures.

Citation Information

Patent Citations

  • Renewable concrete and preparation method thereof

    CN110436837A

  • Recycled concrete and preparation method thereof

    CN111039624A

  • Multi-band-gap combined regulation concrete metamaterial structure and preparation method thereof

    CN115432974A

  • Method for strengthening recycled aggregate

    CN115893891A

  • Preparation method of high-strength recycled aggregate concrete

    CN116693240A